Why do people stick to Facebook web site? A value theory-based view - Yang, Heng-Li; Lin, Chien-Liang (Information technology & people (West Linn, Or.), 2014)
Purpose – Based on past study, three different value constructs, including social value, hedonic value, and epistemic value, were adopted in this study to examine their influence on individual's stickiness to use Facebook. Besides, this paper aims to explore how “trust” affects the personal usage behaviors. Design/methodology/approach – The research model was tested with data from 345 Facebook's users using a web survey. The partial least squares technology was used to test the proposed hypotheses. Findings – Results confirmed that hedonic value served as important value concerns for Facebook users. Besides, considering trust factor, the respondents can be classified into two groups. In the high-trust group, social value and hedonic value produced significant impacts on stickiness. In the low-trust group, the statistical results show that epistemic value and hedonic value had impacts on the stickiness for Facebook web site use, but social value aspect had no significant impact. Research limitations/implications – The respondents were mainly the subjects that belonged to the young age group in Taiwan. Therefore, it should be cautious to generalize the conclusions to other areas or the elder. Practical implications – This study results facilitate web site operators and marketing researchers to understand what value factors and trust affect the user stickiness of Facebook. Their marketing plan and application plug-in can be accordingly adjusted. Originality/value – This study provides positive evidences how value factors affect Facebook stickiness. The paper also proved that high-trust and low-trust people have different value models.